دور نظم المعلومات في تحسين تنافسية الشركات دراسة حالة شركة نفطال _ بسكرة - نسرين, أ.فكرون (Recherches économiques et managériales, 2015)
هدفت الدراسة الى الكشف عن دور نظم المعلومات في تحسين تنافسية الشركات دراسة حالة شركة نفطال بسكرة، لتحقيق اهداف البحث قامت الباحثة بتصميم استبانة شملت(45) فقرة لغرض جمع المعلومات الاولية من عينة الدراسة وعلى ضوء ذلك تم جمع البيانات وتحليلها واختبار الفرضيات باستعانة ببرنامج الحزم الاحصائية للعلوم الاجتماعية SSPSV16  حيث تكون مجتمع الدراسة من 51 اطارا ولقد تم المسح الشامل لجميع مفرداته ،واستخدام العديد من الاساليب الاحصائية لمعالجة البيانات منها معامل الارتباط ومعامل التحديد، المتوسط الحسابي ومعامل الثبات والصدق وغيرها، وبعد اجراء التحليل واختبار فرضياتها توصلت الدراسة الى العديد من النتائج من اهمها انه يوجد دور لنظم المعلومات في تحسين تنافسية الشركات عند مستوى دلالة (0,05). الكلمات الدالة: نظم المعلومات ،موارد نظم المعلومات ،التنافسية ،أبعاد الميزة التنافسية Summary : The study aimed to reveal the role of information systems in improving the competitiveness of companies case study company NAFTAL Biskra, to achieve the goals of research, the researcher designed questionnaire included (45) paragraph for the purpose of gathering initial information from the study sample and the light that has been collecting and analyzing data and testing hypotheses with help program of statistical packages social Sciences SSPSV16 where the study population consisted of 51 frame and has been a comprehensive survey of all the vocabulary, and the use of many of the statistical methods for data processing, including correlation coefficient and the coefficient of determination, the arithmetic mean and coefficient of consistency and honesty, etc., and after conducting the analysis and testing of hypotheses, the study found many of the results of the most important that there is the role of information systems in improving the competitiveness of companies at the level of significance (0.05). Keywords : information systems, information systems resources, competitiveness, the dimensions of competitive advantage